Kuat Tekan Beton Dan Waktu Ikat Semen Portland Pozzolan - R Arianto; Alex Kurniawandy; Ermiyati Ermiyati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Concrete material applied widely as a building material. Development of building construction encourage cement industri to create new types of products. One of types is Portland Pozzolan Cement (PPC). This study aims to determine value of setting time, compressive strength and age factors base on cement variations using Portland Pozzolan Cement  and Portland Type 1 cement. Specimens are made in cylindrical shape with diameter 15 cm and high 30 cm. Testing of these specimens are conducted in age 3, 7, 14, 21, 28 and 90 days which are 10 samples per each variations. Mix composition of concrete is designed by ACI method with compression target in 25 MPa. Result of experiments, initial setting time is 92.99 minutes and final setting time is 150 minutes for cement Type 1, whereas cement PPC shows initial setting time is 121.38 minutes and final setting time is 180 minutes. The averages of compressive strength are 16.99, 22.65, 28.99, 32.89, 38.16 in age 3, 7, 14, 21, 28, 90 respectively for cement Type 1. On the other sides, for cement PPC, the averages are 16.56, 19.28, 25.79, 24.63, 24.66, 30.35 respectively with age. The age factors of Type 1 cement are 0.516, 0.688, 0.881, 0.981, 1.000, 1.160, and the age factor for PPC cement are 0.672, 0.782, 1.046, 0.999, 1.000 and 1,231.  Key word: age factor, compressive strength, PPC, setting time.